(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the article is to assess the level of the financial situation of seaside communities in Poland in 2013-2017. The work uses secondary data from the Ministry of Finance. The level of the financial situation was determined by the synthetic indicator method based on the average values (from 2013-2017) of selected features. The following features were taken into account in the analysis: share of own income in total income, share of operating surplus in total income, share of capital expenditure in total expenditure, self-financing ratio, operating surplus per capita, total liabilities per capita, share of total liabilities in total income and tax per capita (DPPC). The analysis of the financial situation showed that seaside rural and urban-rural communes of theoretically similar nature are significantly diversified in financial aspects.